Promotion of Horizontal Themes and Secondary Objectives within the Project Active Measures to Increase the Participation in Entrepreneurial Tertiary Education of Students from Disadvantaged Environments Antre_S - Carmen Olguta BREZULEANU (Dunarea de Jos University of Galati, 2021)
This article aims to present the ways in which the project "Active measures to increase the participation in entrepreneurial tertiary education of students from disadvantaged environments Antre_S" POCU / 379/6/21 / 12438 carried out by „Ion Ionescu de la Brad ” University of Agricultural Sciences and Veterinary Medicine Iași as an Applicant in partnership with the University of Agricultural Sciences and Veterinary Medicine of Banat„ King Mihai I of Romania ”from Timișoara (Partner 1) and „ Dunărea de Jos ” University Galați (Partner 2), contributes to the accomplishment of the homework secondary and ESF horizontal objectives. Targeted by the Applicant's Guide - Specific Conditions "Entrepreneur Student Scholarship".